Cost benefit analysis of kenaf cultivation for producing fiber in Malaysia - Md Thair, Paridah; Abdelrhman Mohammed, Hamdon Ali; Othman, Mohd Shahwahid (OMICS International, 2017)
The main objective of this work to assess the cost benefit of kenaf cultivation in Malaysia. The data were collected through the focus group discussion with kenaf farmers as well as from National Company of Kenaf and Tobacco board (NKTB) administrative staff, the production data collected from Kenaf Processing and Marketing Centre Bachok-Kelantan. The cost benefit analysis model was developed using Microsoft Excel software. Three scenarios of kenaf production per hectare were considered which were 15, 12 and 10 ton. According to the data analysis; the investigation of the three scenarios revealed that when the farmers in Kelantan state cultivated kenaf for producing fiber the production of 15 tons per hectare was found to be viable and maximizes their profit. The results suggest that farmers need to increase the productivity and alternate the current cultivated variety V36 with the tested varieties in Malaysian soils.